Local Botanical Knowledge about Sideroxylon obtusifolium (Roem. & Schult.) T.D.Penn. in Rural Communities in the Semi-Arid Region of Brazil - Pedrosa, Kamila Marques; Lima, Elizabethe Quintella de; Lucena, Camilla Marques; Carvalho, Thamires Kelly Nunes; Ribeiro, João Everthon da Silva; Marín, Edna Arévalo; Oliveira, Rodrigo Silva de; Alves, Ricardo Elesbão; Silva, Silvanda de Melo; Cruz, Denise Dias da; Lucena, Reinaldo Farias Paiva (Ethnobotany Research and Applications, 2015)
Sideroxylon obtusifolium (Roem. & Schult.) T.D.Penn. is a species widely used, for several purposes, by traditional populations from the semi-arid region of Brazil. This study records the knowledge and use attributed to this species by residents from two regions: the Curimataú (Coelho and Capivara communities) and the Cariri (São Francisco and Santa Rita communities) located in the semi-arid region of Paraíba State, Northeast Brazil. We interviewed all householders (244 informants) through a semi-structured form. The data were organized in eight use categories, and comparisons were made using a Mann-Whitney test and a Kruskal-Wallis test. Medicinal was the most cited use. To test the similarity in medicinal uses, we used a one-way ANOSIM permutation test. Knowledge about plant use was similar in both communities but differed by gender. Bark was the most used part for medicinal purposes, and “undefined diseases or undefined pains” was the most cited bodily system-ailment. Specific needs in each community determined how plants were employed.